POLITICAL WILL WALIKOTA DALAM MEMUTUS PENYEBARAN CORONA VIRUS DISEASE 2019 DI KOTA PEKANBARU - Adlin Adlin; Erman Muchtar; Sofyan Hadi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The number of residents who indicated positive for Corona Virus Desaese 2019 (Covid-19) in Pekanbaru from March 2020 to October 2020 jumped sharply. In order to stop the spread of Covid-19 there has been a Political will of the Mayor of Pekanbaru which can be seen clearly from the initiatives and policy choices made. A total of 12 policies consisting of regulations, circulations and decisions have been made by the Mayor of Pekanbaru, but positive cases of Covid-19 tend to fluctuate. This article aims to describe the initiatives and policy choices made by the Mayor of Pekanbaru and to analyze the factors that influence the policy choices made that have not been effective in deciding the spread of Covid-19 in Pekanbaru City. The research method used a qualitative approach using literature studies. The results showed that the Mayor of Pekanbaru's initiatives and policy choices were too influenced and imitated central government policies. As an organization, the city of Pekanbaru does not have any proven institutions and procedures to deal with disasters, plus individually, the attitude of the Pekanbaru mayor seems to be careless and panicked in facing Covid-19. The situation is increasingly unfavorable due to a weak sense of trust and the emergence of confusion in the community due to policies related to Covid-19 which are often changed by the Pekanbaru city government.